An integrated evaluation framework for evaluating renewablebased building sector implementation in remote/off grid areas with varying climatic zones - Maryam, Rida (400544); Supervisor: Dr. Syed Ali Abbas Kazmi (Islamabad : USPCAS-E, NUST, 2025)
TH-629
Keywords: MS EEP Thesis; MS Thesis